Glyoxalase 1, regulated by LncRNA MALAT1, promotes malignant development of esophageal squamous cell carcinoma - Guo, Zhong (Int J Clin Exp Pathol, 2018)
In previous study we found that long noncoding RNA (lncRNA) MALAT1 promotes proliferation and metastasis of esophageal squamous cell carcinoma (ESCC), and that the following microarray chip screening of MALAT1 target genes showed that Glyoxalase I (GLO1) was a potential downstream effector of MALAT1. In this study, we further confirmed that GLO1 was regulated by MALAT1. GLO1 belongs to the glyoxalase system, which encodes a ubiquitous detoxification pathway being implicated in the progression of multiple malignancies. However, currently, the role of GLO1 in human ESCC remains unclear. To explore the clinical significance of GLO1 in ESCC, we first determined the expression of GLO1 in 40 paired ESCC tissues and adjacent normal tissues. We found that the expression level of GLO1 was higher in human ESCC tissues (P=0.0040). Knockdown of GLO1 by siRNA significantly inhibited the proliferation and migration of ESCC cells. In vivo assays showed that knockdown of GLO1 decreased tumor growth. Overall, GLO1 might be an essential effector of lncRNA MALAT1 which promotes ESCC progression and can be identified as a potential therapeutic target for ESCC in the future.